2020
DOI: 10.3389/fimmu.2020.01544
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Supplementation of Dietary Arginine and Citrulline Modulates Gilthead Seabream (Sparus aurata) Immune Status

Abstract: Several amino acids (AA) are known to regulate key metabolic pathways that are crucial for immune responses. In particular, arginine (ARG) appears to have important roles regarding immune modulation since it is required for macrophage responses and lymphocyte development. Moreover, citrulline (CIT) is a precursor of arginine, and it was reported as an alternative to ARG for improving macrophage function in mammals. The present study aimed to explore the effects of dietary ARG and CIT supplementation on the gil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…In the present study, data from the analyzed responses of fish fed supplemented diets suggest that the effects of Thr, His, and Tau supplementation on fish immune system seem to be of an indirect nature, when compared with other EAAs previously studied such as tryptophan, methionine, or arginine [ 32 , 61 , 62 ], which present stronger and more direct effects. In a previous work where the effects of dietary tryptophan supplementation were also explored in gilthead seabream, only a transient immune enhancement was observed in fish fed an extreme formulation (no FM inclusion) over a short-term feeding period (two weeks), suggesting that these putative advantageous effects seem to disappear over a longer feeding period (13 weeks) [ 33 ].…”
Section: Discussionmentioning
confidence: 42%
See 2 more Smart Citations
“…In the present study, data from the analyzed responses of fish fed supplemented diets suggest that the effects of Thr, His, and Tau supplementation on fish immune system seem to be of an indirect nature, when compared with other EAAs previously studied such as tryptophan, methionine, or arginine [ 32 , 61 , 62 ], which present stronger and more direct effects. In a previous work where the effects of dietary tryptophan supplementation were also explored in gilthead seabream, only a transient immune enhancement was observed in fish fed an extreme formulation (no FM inclusion) over a short-term feeding period (two weeks), suggesting that these putative advantageous effects seem to disappear over a longer feeding period (13 weeks) [ 33 ].…”
Section: Discussionmentioning
confidence: 42%
“…Moreover, Ramos-Pinto, Azeredo, Silva, Conceição, Dias, Montero, Torrecillas, Silva and Costas [ 32 ] described that arginine and citrulline, particularly when supplemented at a 1% of feed inclusion level, induced a stimulation of the fish immune system after a short-term feeding period, verified mostly by a modulation of the gilthead seabream plasma proteome and health-biomarkers after four weeks of exposure. Hence, the fact that arginine concentration was higher in the CTRL diet compared to the others could have translated into an increased gilthead seabream immune status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was clearly shown that inflammation suppressed by the effects of tryptophan than methionine, with a notable downregulation in mmp9 and IL-1β of juvenile European seabass ( 25 ). Arginine was confirmed to have no remarkable alteration for the inflammatory process but in IL-10 and IL-34 regulation in the head kidney of juvenile gilthead seabream ( 26 ). Thus, different effects addressed on immunoregulation by amino acids might be diverse in fish.…”
Section: Introductionmentioning
confidence: 95%
“…In fish, arginine may function in immune responses in multiple ways including producing NO and polyamines, directly modulating gene expression, and regulating nutrient availability of immune cells. A recent study also uses the shotgun proteomics technique to reveal the candidate serum proteins involved in fish immune responses after dietary arginine supplementation ( Ramos-Pinto et al., 2020 ). Both in vivo and in vitro experiments with channel catfish showed that arginine supplementation improved the abilities of macrophage killing and phagocytosis, increased the lysozyme activity and erythrocyte number, and enhanced the proliferation of native lymphocytes after mitogenic exposure ( Buentello et al., 2007 ; Pohlenz et al., 2012 ).…”
Section: Arginine Immunonutrition In Fishmentioning
confidence: 99%